A phase 1/2a study to test the safety and immunogenicity of a p16INK4a peptide vaccine in patients with advanced human papillomavirus-associated cancers - Reuschenbach, Miriam; Kloor, Matthias; Prigge, Elena-Sophie; Sauer, Madeleine; Knebel Doeberitz, Magnus von (Cancer, 2016)
BACKGROUND The cyclin-dependent kinase inhibitor p16INK4a is strongly and consistently overexpressed in all human papillomavirus (HPV)-associated cancers. Therefore, the authors hypothesized that p16INK4a may be a vaccine target antigen for HPV-associated cancers. To test this hypothesis, the authors performed a phase 1/2a first-in-human trial to evaluate the safety and immunogenicity of a p16INK4a-based peptide vaccine. METHODS A total of 26 patients with different, advanced, p16INK4a-overexpressing, HPV DNA-positive cancers were included after the completion of standard treatment. According to protocol, 12 subcutaneous injections of a p16INK4 peptide (P16_37-63) mixed in a water-in-oil emulsion with immunoadjuvant activity (Montanide ISA-51 VG) were administered over a 6-month period. RESULTS A total of 20 patients received at least 4 injections and were evaluable for immune responses against P16_37-63. Clusters of differentiation (CD) 4 T cells were detected in 14 of 20 patients (3 of whom had preexisting CD4 T cells before vaccination), CD8 T cells were detected in 5 of 20 patients, and antibodies were detected in 14 of 20 patients (1 of whom had preexisting antibodies). No suspected unexpected serious adverse reaction or serious adverse drug reaction was documented. All reported serious adverse events were expected and not considered to be related to study therapy. None of the patients discontinued trial participation due to unacceptable toxicities and no dose-limiting toxicities occurred. Tumor response could be assessed in 14 patients. Of these, 9 patients (64%) had stable disease as their best overall response and 5 patients (36%) developed progressive disease. CONCLUSIONS Vaccination with the p16INK4a-derived peptide P16_37-63 appears to induce cellular and humoral immune responses and does not cause severe toxicities. The results of the current study pave the way for the further clinical development of p16INK4a-based cancer immunotherapeutics. Cancer 2016;122:1425-1433. © 2016 American Cancer Society.
Gesehen am 18.10.2019
Im Titel ist "INK4a" in p16INK4a hochgestellt